(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
This paper focuses on the recovery and the enrichment of philological-critical investigations on Eighteenth Century literature. The studies of the manuscripts of Parini’s Giorno and the new national edition of Goldoni’s theater seem to have contributed to reinforce the philological studies on Modern Literature. Some of these studies that have gone through and perhaps are still going through a period of crisis for different reasons, as the close of historical collections and the lack of resources of the national editions. It has also influenced the prevalence of other methods less attentive to the philological questions and perhaps an excessive predilection for the contemporary context.